1998
DOI: 10.1177/097168589800400202
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership in Three Dimensions

Abstract: Is an ethical leader an oxymoron? Society demands and expects greater accountability from organizational leaders. The literature on leadership, especially business leadership, has neglected ethical issues by focusing only on those approaches and strategies that emphasize self-centred, individualistic concerns. How ever, true and effective leadership is one in which the leader's behaviour and the exercise of the leadership influence process are consistent with ethical and moral values. The authors argue that ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 1 publication
2
23
0
Order By: Relevance
“…This is supported to some extent by data showing that a leadership style that is supportive and promotes autonomy, which would be consistent with transformational leadership, enhances intrinsic motivation (Richer & Vallerand, 1995). This empowering process is thought to increase followers' self-efficacy and capacity for selfdetermination (Kanungo & Mendonca, 1998). One objective of the present study is to verify the self-determination claim.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…This is supported to some extent by data showing that a leadership style that is supportive and promotes autonomy, which would be consistent with transformational leadership, enhances intrinsic motivation (Richer & Vallerand, 1995). This empowering process is thought to increase followers' self-efficacy and capacity for selfdetermination (Kanungo & Mendonca, 1998). One objective of the present study is to verify the self-determination claim.…”
supporting
confidence: 54%
“…Ryan,Mims,and Koestner (1 983) suggested that the controlling aspect of rewards decreases intrinsic motivation (see Rummel & Feinberg, 1988, for a discussion of cognitive evaluation theory). However, transformational leaders are known to empower rather than control their followers (Kanungo & Mendonca, 1998). This is supported to some extent by data showing that a leadership style that is supportive and promotes autonomy, which would be consistent with transformational leadership, enhances intrinsic motivation (Richer & Vallerand, 1995).…”
mentioning
confidence: 92%
“…The moral potential of authentic leadership has long captured the interests of scholars (Bass and Steidmeier 1999;Howell and Avolio 1992;Kanungo and Mendonça 1998). As authentic leaders have a clear, internalized moral perspective and engage in balanced decision making, they clearly possess the capacity to take moral-driven action.…”
Section: Authentic Leadership Machiavellianism and Moral Actionmentioning
confidence: 99%
“…There appears to be some relationship between Karma-Yoga and transformational leadership. Kanungo and Mendonca (1998) discussed moral duties that benefit social order at the cost of considerable personal sacrifice and talked about life as a process of becoming non-egoistic and stable-minded for ethical leaders. The link between transformational leadership and morality was one of the basic premises of Burns (1978).…”
Section: Introductionmentioning
confidence: 99%